Macrophyte habitat architecture and benthic-pelagic coupling: Photic habitat demand to build up large P storage capacity and bio-surface by underwater vegetation - Teubner, Katrin; Teubner, Irene E.; Pall, Karin; Tolotti, Monica; Kabas, Willi; Drexler, Silke-Silvia; Waidbacher, Herwig; Dokulil, Martin T. (Frontiers in Environmental Science, 2022)
Macrophytes play an important role in shallow lake ecosystems if large standing crop can be achieved. We focus on how macrophyte growth became stimulated by underwater light climate in the oxbow lake Alte Donau (Austria) during lake restoration, and on the ecological importance beyond the achieved macrophyte yield. The year-to-year progression of macrophyte yield could be traced by the achievement of optimum light requirements (12% surface ambient light, ). After phosphate precipitation treatment, the photic>12% pelagic habitat accounted for more than half of the total water volume in summer, while the achievement of the same photic>12% conditions for half of the total sediment surface area was delayed by 8 years. A delay in the light exposure for the lake bottom area compared to the lake water volume is related to the basin morphometry, but the time span that is required for passing this delay depends on the efficiency of the restoration measures. The 8-year delay means that lake restoration of Alte Donau with the focus on macrophyte re-establishment was difficult to get going, as it needed to be stimulated by optimum light conditions at the lake bottom. A further increase of photic>12% conditions to more than 3/4 size of both the pelagic and the benthic habitat was associated with a sustained macrophyte yield. With the onset of this large biomass yield, the phosphorus storage pool of macrophytes exceeded for the first time the annual peak concentration of total phosphorus of the whole lake water by about one order of magnitude. At a spatial scale, the macrophyte bio-surface exceeded the size of the lake bottom surface also by about one order of magnitude. We discuss macrophytes as a sink of phosphorus by retaining this nutrient element at least during the growing season. We further see the immensely large macrophyte bio-surface as a vast spatial dimension for an additional habitat. Therefore, we conclude that mature macrophyte formations need to be considered not only as biomass yield, but create a unique macrophyte habitat architecture as a third main component in the network between the benthic and pelagic habitat in lakes.